Managing Bipolar Disorder in Clinical Practice - Vieta, Eduard. (Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2013)
Written by Eduard Vieta, a world renowned award winning expert in this field, Managing Bipolar Disorder in Clinical Practice, Third Edition, is an up-to-date, concise practical handbook developed with the clinician in mind. Including the most recent clinical guidelines, including the British Association for Psychopharmacology (BAP) and Canadian Network for Mood and Anxiety Treatments (CANMAT) guidelines, this handbook is intended to highlight every major aspect of this serious mental health disorder, including assessment, treatment, long-term management, and recent developments.